Taxes and Tradable Permits As Instruments for Controlling Pollution : Theory and Practice - Norregaard, John (IMF Working Papers; Working Paper ;, 2000)
This paper examines the relative merits of two dominant economic instruments for reducing pollution-'green' taxes and tradable permits. Theoretically, the two instruments share many similarities, and on balance, neither seems preferable to the other. In practice, however, most countries have relied more on taxes than on permits to control pollution. The analysis suggests a number of lessons to be learned from country experiences regarding the design and implementation of both instruments. While many, particularly European countries, currently have long-term programs involving environmental taxes, a willingness to experiment with tradable permits seems to be growing, especially given the Kyoto protocol emission targets.